Effect of local own source revenue, general allocation funds, special allocation funds, and profit-sharing funds on capital expenditures - Marselina Ariany Pekambani; M. E. Perseveranda; Rere Paulina Bibiana (Institute of Computer Science (IOCS), 2023)
This study's goal was to determine how local own-source income, general funds, special funds, and profit-sharing funds affected the capital expenditures of the East Nusa Tenggara provincial government and 22 districts and cities throughout the province. Using probability sampling, the local government budgets of 22 regencies or cities for the 2019–2022 fiscal year and the local government budget of the NTT Provincial Government serve as the study's population. Results, local own-source income, general allocation funds, and profit sharing have a considerable and favorable influence on capital investment in the province of East Nusa Tenggara. The variable special allocation funds in East Nusa Tenggara Province affect capital expenditures positively but not statistically significantly, whereas the entire set of study factors affect capital expenditures positively and statistically significantly.